2012
DOI: 10.5966/sctm.2012-0015
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Autologous Mesenchymal Stem Cell-Derived Neural Progenitors as a Feasible Source of Stem Cells for Central Nervous System Applications in Multiple Sclerosis

Abstract: ABSTRACT

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
59
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 64 publications
(61 citation statements)
references
References 51 publications
2
59
0
Order By: Relevance
“…The protocol has been tested in nonhuman primates and human patients who receive intravenous injections of their own BMSCs (34,40,46). The results show neuroprotection, neurotrophic effects, and anti-inflammatory responses after transplantation therapy (20,22). In preclinical laboratories, BMSCs have been considered a promising cell source for treatment of many diseases, including ischemic stroke (15,63), traumatic brain injury (60), intracerebral hemorrhage (62), subarachnoid hemorrhage (31), spinal cord injury (33), and other neurodegenerative disorders (2,29,39,42).…”
Section: Discussionmentioning
confidence: 99%
“…The protocol has been tested in nonhuman primates and human patients who receive intravenous injections of their own BMSCs (34,40,46). The results show neuroprotection, neurotrophic effects, and anti-inflammatory responses after transplantation therapy (20,22). In preclinical laboratories, BMSCs have been considered a promising cell source for treatment of many diseases, including ischemic stroke (15,63), traumatic brain injury (60), intracerebral hemorrhage (62), subarachnoid hemorrhage (31), spinal cord injury (33), and other neurodegenerative disorders (2,29,39,42).…”
Section: Discussionmentioning
confidence: 99%
“…On another tone, MSC transplantations used for tissue repair purposes and transplantations have been performed for the treatment of skeletal fractures, osteoarthritis, cancer, hemorrhages, liver failure, ischemic heart failure, and chronic otitis, among others. [74][75][76][77][78][79] Recent systematic review papers based on meta-analysis data suggest that transplantation of bone marrow MSCs in patients with acute myocardial infarction or chronic ischemic heart disease is safe and associated with slight improvement in left ventricular function, left ventricular end systolic volume, and decreased infarct size when compared to state of the art therapy. 80,81 However, both meta-analyses suggested that individual trials have not yet been large enough to reliably explore the outcomes.…”
Section: Mscs In Clinical Trialsmentioning
confidence: 99%
“…In addition, placental MSCs via reduced production of the anti-inflammatory proteins such as TNF-α-stimulated gene/ protein 6 (TSG-6) in inflammatory regions, have therapeutic effects in mice with EAE [19]. Other studies have shown the therapeutically benefit of BM-MSCs [20,21] In contrast with these studies, Nessler et al, showed that intravenously administration of human BM-MSCs has no effects on remyelination process and glial cell reactions in cuprizone model of MS because these cells were not able to cross the blood-brain barrier [26]. Thus, adipose-derived stem cell (ADSCs) as a suitable cell source has attracted attention…”
Section: Stem Cells Transplantation In Demyelinating Diseasesmentioning
confidence: 99%